Optimizing performance of search engines based on user behavior - Jkr Sastry, Dr; Sri Harsha Vamsi, M; Srinivas, R; Yeshwanth, G (International Journal of Engineering and Technology, 2018)
WEB clients use the WEB for searching the content that they are looking for through inputting keywords or snippets as input to the search engines. Search Engines follows a process to collect the content and provide the same as output in terms of URL links. One can observe that only 20% of the outputted URLS are of use to the end user. 80% of output is unnecessarily surfed leading to wastage of money and time. Customers have surfing characteristics which can be collected as the user keep surfing. The search process can be made efficient by including the user characteristics / Behaviors as part and parcel of search process. This paper is aimed at improving the search process through integration of the user behavior in indexing and ranking the web pages.